Medical Record System For Pregnancy Antenatal Care - Azhar, Aina Hawani; Sari, Suhaila; Mohd Taujuddin, Nik Shahidah Afifi; Hazli Roslan; Nabilah Ibrahim (Evolution in Electrical and Electronic Engineering, 2020)
Nowadays, medical aspects seem to become more important in human being life as all types of ages, but the process of managing the medical record is longer in terms of time taken for an appointment. Therefore, this project aims to develop the medical record system for pregnancy antenatal care, which helps in reducing the time process of managing the medical record in the government health clinics. The images of the medical record are captured using the camera mobile phone, upload, retrieve, display and delete in the developed an application that is also connected to the database platform to store the images uploaded. The performance of the proposed method is evaluated through recording time taken to complete whole process in application. The proposed method provides excellent results, as the time taken for completing the whole process in the application did not exceed nine minutes. The result shows that the proposed method may have a potential contribution to overcome the problems in managing the medical record for pregnancy antenatal care in government health clinics and in order to increase the performance of the system, the real testing of application should be conducted on the health clinic staff to collect the real-time process using the developed system.